Effect of the temperature on the luminescence profile of photonic materials for biological applications - Sadowska, Karolina; Żmojda, JacekM Ariusz (Photonics Letters of Poland, 2023)
Temperature has a significant impact on the luminescence profile of photonic materials for biological applications. This paper presents the effect of temperature on the luminescence profile of three different photonic materials in the range of the second biological window. The effect of temperature on luminescence properties is shown on glass, glass-ceramics, and phosphors co-doped with Eu3+/Nd3+/Yb3+ under UV laser diode excitation. Each sample has been analyzed for temperature effects on optical parameters in biological window ranges. Moreover the effect of temperature on mechanisms of energy transfer Eu3+ → Nd3+ → Yb3+ in all fabricated photonic materials was analyzed. Full Text: PDF References J. Zhou, J.L. Leano Jr., Z. Liu, D. Jin, K.-L. Wong et al., "Impact of Lanthanide Nanomaterials on Photonic Devices and Smart Applications", Small 14, 1801882 (2018). CrossRef Z. Li, Y. Zhang, G. Han, "Lanthanide-Doped Upconversion Nanoparticles for Imaging-Guided Drug Delivery and Therapy", Springer Series in Biomaterials Science and Engineering 6, 139 (2016). CrossRef A. Zhang, Z. Sun, M.Jia, et al., "Simultaneous luminescence in Ⅰ, Ⅱ and III biological windows realized by using the energy transfer of Yb3+→Er3+/Ho3+→Cr3+", Chemical Engineering Journal 365, 400 (2019). CrossRef M.-F. Tsai, S.-H.G. Chang, F.-Y. Cheng, V. Shanmugam, Y. Cheng et al., "Au Nanorod Design as Light-Absorber in the First and Second Biological Near-Infrared Windows for in Vivo Photothermal Therapy", ACS Nano 7, 5330 (2013). CrossRef S. Ding, L. Lu, Y. Fan, F. Zhang, "Recent progress in NIR-II emitting lanthanide-based nanoparticles and their biological applications", J. Rare Earth. 38, 451 (2020). CrossRef U. Rocha, K.U. Kumar, C. Jacinto, I. Villa, F. Sanz-Rodriguez et al., "Neodymium-Doped LaF3 Nanoparticles for Fluorescence Bioimaging in the Second Biological Window", Small 10, 1141 (2014). CrossRef M. Jia, Z. Sun, H. Xu, X. Jin, Z. Lv et al. "An ultrasensitive luminescent nanothermometer in the first biological window based on phonon-assisted thermal enhancing and thermal quenching", J. Mater. Chem. C 8, 15603 (2020). CrossRef H. Lin, T. Hu, Y. Cheng, M. Chen, Y. Wang, "Glass Ceramic Phosphors: Towards Long-Lifetime High-Power White Light-Emitting-Diode Applications–A Review", Laser Photonic Rev. 12, 1700344 (2018). CrossRef H. Su, Y. Nie, H. Yang, D. Tang, K. Chen, T. Zhang, "Improving the thermal stability of phosphor in a white light-emitting diode (LED) by glass-ceramics: Effect of Al2O3 dopant", J. Eur. Ceram. Soc. 38, 2005 (2018). CrossRef Kenry, Y.Duan, B. Liu, "Recent Advances of Optical Imaging in the Second Near-Infrared Window", Adv. Mater. 30, 1802394 (2018). CrossRef M.L. Debasu, H. Oliveira, J. Rocha, L.D. Carlos, "Colloidal (Gd0.98Nd0.02)2O3 nanothermometers operating in a cell culture medium within the first and second biological windows", J. Rare Earth. 38, 483-491 (2020). CrossRef L. Pavasaryte, A. Katelnikovas, V. Klimavicius, V. Balevicius, A. Krajnc et al., "Eu3+-Doped Y3−xNdxAl3O12 garnet: synthesis and structural investigation", Phys. Chem. Chem. Phys. 19, 3729 (2017). CrossRef K. Sadowska, P. Awramiuk, I Zgłobicka, K Rećko, J. Żmojda, "Quantum efficiency of europium doped LaPO4 phosphors for UV sensing applications", Photonics Lett. Poland 14, 28 (2022). CrossRef P. Lei, J. Feng, H. Zhang, "Emerging biomaterials: Taking full advantage of the intrinsic properties of rare earth elements", Nano Today 35, 100952 (2020). CrossRef K. Sadowska, T. Ragiń, M. Kochanowicz, P. Miluski, J. Dorosz, et al., "Analysis of Excitation Energy Transfer in LaPO4 Nanophosphors Co-Doped with Eu3+/Nd3+ and Eu3+/Nd3+/Yb3+ Ions", Materials 16, 1588 (2023). CrossRef